2020
DOI: 10.1093/ntr/ntaa047
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Randomized Clinical Trial of Brief Interventions to Encourage Quit Attempts in Smokers From Socioeconomic Disadvantage

Abstract: Introduction Cigarette smoking disproportionately affects communities of low socioeconomic status where greater smoking prevalence and poorer cessation rates have been observed. Utilizing brief evidence-based interventions to increase cessation attempts may be an effective and easily disseminable means by which to mitigate undue burden in this population. Aims and Methods The current intervention randomized daily smokers (N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(41 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Characteristics and fndings of the eight included studies [52][53][54][55][56][57][58][59] are displayed in Table 3. Seventy-fve percent of the included studies measured smoking behaviour [52][53][54][55][56][57], and the remaining two studies measured factors related to diet [58,59] and exercise [58]. Te included studies were a mixture of TSE settings [54,[57][58][59] and TSE service providers [52,53,55,56,58].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics and fndings of the eight included studies [52][53][54][55][56][57][58][59] are displayed in Table 3. Seventy-fve percent of the included studies measured smoking behaviour [52][53][54][55][56][57], and the remaining two studies measured factors related to diet [58,59] and exercise [58]. Te included studies were a mixture of TSE settings [54,[57][58][59] and TSE service providers [52,53,55,56,58].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Seventy-fve percent of the included studies measured smoking behaviour [52][53][54][55][56][57], and the remaining two studies measured factors related to diet [58,59] and exercise [58]. Te included studies were a mixture of TSE settings [54,[57][58][59] and TSE service providers [52,53,55,56,58]. TSE settings ranged from churches [58,59], homeless shelters [54], and a food bank [57], and TSE service providers were often peers such as fellow veterans [52] or church attenders [58], although some were volunteers from voluntary organisations [55,56] such as girl guides [53].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies used a randomized controlled trials design with one or another trial feature, including allocation concealment and blinding. Of the 12 studies, 3 studies used brief intervention or brief advise, (30,32,35,38,41) 6 studies used motivational interviews, (15,30,33,34,37,40) and one study used brief counseling on harm to self and harm to others (39) and quit immediately award model based on brief intervention approach. Seven of the 12 studies (58.3%) reported a beneficial effect of brief advice or motivational interview on reducing tobacco use (Table 2).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…However, the same study reported increased cessation of medication use, motivation, and confidence to quit compared to brief advice, which further indicates the effectiveness of MI in behavior changes to quit smoking. In a study (34) at a Northeastern US State, daily smokers attended brief motivational interviewing and significantly reduced cigarette use. Likewise, motivational interviewing effectively improved quitting smoking among nurses over brief advice in a study conducted in Spain.…”
Section: Motivational Interviewing (Mi)mentioning
confidence: 99%